2009
DOI: 10.1097/iae.0b013e3181985915
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month Safety and Visual Acuity Results From a Feasibility Study of Intraocular, Epiretinal Radiation Therapy for the Treatment of Subfoveal CNV Secondary to Amd

Abstract: The short-term safety and efficacy of intraocular, epiretinal delivery of beta radiation for the treatment of subfoveal choroidal neovascularization was promising in this small study group and should be studied in a larger cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 39 publications
1
42
0
6
Order By: Relevance
“…At 12 months, all patients lost \3 lines and 5 of 17 patients in the 24 Gy group gained C3 lines. There were no adverse effects due to the radiation [61]. Mean change in VA at month 12 was ?10.3 letters in the 24 Gy and -1.0 letters in the 15 Gy cohort.…”
Section: Epimacular Brachytherapy (Embt) In Amdmentioning
confidence: 96%
“…At 12 months, all patients lost \3 lines and 5 of 17 patients in the 24 Gy group gained C3 lines. There were no adverse effects due to the radiation [61]. Mean change in VA at month 12 was ?10.3 letters in the 24 Gy and -1.0 letters in the 15 Gy cohort.…”
Section: Epimacular Brachytherapy (Embt) In Amdmentioning
confidence: 96%
“…Epimacular brachytherapy is undertaken as a one-off treatment and has been reported in Phase II trials. 2,3 These feasibility studies showed promising short-term results compared with anti-VEGF monotherapy, and there are two large, pivotal, randomized controlled trials under way-CABERNET and MERLOT. The former study investigates treatment-naive patients, the latter, patients who are already receiving anti-VEGF pharmacotherapy.…”
mentioning
confidence: 97%
“…While the first study demonstrated that a minimum dose of 24 Gy is required to achieve a therapeutic effect [14], the other study demonstrated the effect of brachytherapy combined with two injections of bevacizumab [13]. Radiation-induced complications were not reported, and the average increase in visual acuity was 8.9 letters.…”
mentioning
confidence: 97%
“…So far, only phase I/II studies for epiretinal brachytherapy in AMD using the VIDION system have been published [13,14]. While the first study demonstrated that a minimum dose of 24 Gy is required to achieve a therapeutic effect [14], the other study demonstrated the effect of brachytherapy combined with two injections of bevacizumab [13].…”
mentioning
confidence: 98%